Zinc Oxide Nanoparticles Boosts Phenolic Compounds and Antioxidant Activity of Capsicum annuum L. during Germination - García-López, Josué; Zavala-García, Francisco; Olivares-Sáenz, Emilio; Lira-Saldívar, Ricardo; Díaz Barriga-Castro, Enrique; Ruiz-Torres, Norma; Ramos-Cortez, Edith; Vázquez-Alvarado, Rigoberto; Niño-Medina, Guillermo (Agronomy (Basel), 2018)
The effects of zinc oxide nanoparticles on seed germination and seedling growth of Capsicum annuum L. were determined in this research. Total phenols content, total flavonoids, and condensed tannins, as well as 2,2-diphenyl-1-picrylhydrazyl (DPPH) antioxidant capacity was determined. Results indicated that treatment with zinc oxide nanoparticles (ZnO-NPs) improved seed germination rate during the first seven days. The seed vigor germination increased 123.50%, 129.40% and 94.17% by treatment with ZnO-NPs suspensions at 100, 200 and 500 ppm, respectively. The morphological parameters tested revealed that ZnO-NPs treatments did not significantly affect plumule development, but they had a significant impact (p ≤ 0.01) on radicle length. Suspensions at 100, 200 and 500 ppm of ZnO-NPs inhibited seedling radicle growth and promoted accumulation of phenolic compounds, with a phytotoxic effect in this organ. Results suggested that zinc oxide nanoparticles influence seed vigor and seedling development and promoted the accumulation of desirable phenolic compounds in the radicle.